Studi Hermeneutik-Filosofis Teks Lelaku Tapa Wuda Ratu Kalinyamat Sebagai Simbol Pendidikan Agama Islam - Zam Zami, Muhammad Riqfi; Mazaya, Nur Widad; Astuti, Widia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article discusses about the hidden meaning of tapa wuda that had performed by Kalinyamat Queen as a symbol of Islamic education. This ritualistic behavior recorded in the Babad Tanah Jawi text which is often invites controversy about its meanings. Many people interpret tapa wuda textually as